Studi Literatur : Faktor Penyebab Ketidakpuasan Pasien di Pelayanan Pendaftaran Rawat Jalan RSU Haji Surabaya 2020 - Agni Candramawa Sholikha; Rossalina Adi Wijayanti; Novita Nuraini (Politeknik Negeri Jember, 2020)
Patient satisfaction is the result of the patient's assessment of the service received based on truth and reality that is then compared to his expectations. The results of observations made by researchers at Surabaya Haji Hospital based on medical record data on the number of outpatients visiting Surabaya Haji Hospital in January to March 2020 there is a decrease in the number of outpatient visits each month. The purpose of this study was to determine the level of patient satisfaction in the outpatient registration at RSU Haji Surabaya. This study uses a literature review method of 10 journals using measurement techniques of 5 dimensions of health service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of the literature review indicate that the satisfaction of the quality dimension is considered the most satisfied is the dimension of assurance and reliability, while the highest dimension of dissatisfaction is the dimension of tangibles and empathy.